Beseda kot gibljiva tarča - Strehovec, Janez (Jezik in slovstvo, 2002)
The Internet features new forms of textuality based in the specific propertiesof the new media and forms of communication related to it. One of them is web literary objects as a new type of textuality with literary aspirations, based od digital, programmed words and new forms of text decoding. The reader/user is exposed to a new experience of the word as a new- media, software-supported object which entices him to do "mouse reading", a complex activity involving also the sense of touch
Keywords: tekstna lingvistika; internet; spletne strani